2018
DOI: 10.1038/labinvest.2017.112
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic Epstein–Barr virus recruits Nm23-H1 to regulate chromatin modifiers

Abstract: In cancer progression, metastasis is a major cause of poor survival of patients and can be targeted for therapeutic interventions. The first discovered metastatic-suppressor Nm23-H1 possesses nucleoside diphosphate kinase, histidine kinase, and DNase activity as a broad-spectrum enzyme. Recent advances in cancer metastasis have opened new ways for the development of therapeutic molecular approaches. In this review, we provide a summary of the current understanding of Nm23/NDPKs in the context of viral oncogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 101 publications
2
7
0
Order By: Relevance
“…Earlier studies in our lab showed that DNMT3A and DNMT3B, but not DNMT1, gradually increased in EBV primary infected-B cells [37]. Furthermore, studies in our lab showed that EBNA3C not only increased the expression of DNMT1 but also interacted with DNMT1 in EBNA3C-expressing cell lines [56]. In this study, we confirmed that DNMT1 was slightly increased in EBNA3C stably expressing BJAB7 and BJAB10 cell lines.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Earlier studies in our lab showed that DNMT3A and DNMT3B, but not DNMT1, gradually increased in EBV primary infected-B cells [37]. Furthermore, studies in our lab showed that EBNA3C not only increased the expression of DNMT1 but also interacted with DNMT1 in EBNA3C-expressing cell lines [56]. In this study, we confirmed that DNMT1 was slightly increased in EBNA3C stably expressing BJAB7 and BJAB10 cell lines.…”
Section: Discussionsupporting
confidence: 84%
“…Previous data from our lab have shown that EBNA3C could interact with DNMT1 and induce DNMT1 expression [56]. Earlier studies also showed that silencing DNMT1 could upregulate RASSF1A expression and suppress RASSF1A methylation in esophageal squamous cell carcinoma [75].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[48][49][50][51][52][53][54][55] The interactions of NDPK with components of the cytoskeletal machinery are highly relevant, given the well-established role of the cytoskeleton in cell motility, a critical determinant of the metastasis process. NME1 has also been reported to bind proteins belonging to small and heterotrimeric G-proteins ( [56][57][58][59][60][61] ; and Filic 62 upcoming issue; Abu-Taha et al, 63 this issue), transcriptional complexes ( 64-69 ; Sharma et al, 70 Pandey and Robertson, 71 and Puts et al, 72 all in this issue), and components of signaling pathways of MAPK, [73][74][75] TGF-β [76][77][78] and Notch, 79 as well as other factors promoting invasion and metastasis ( 80,81 ; Ferrucci et al 82 upcoming issue). Accordingly, the list of protein/protein interactions involving NME1 is huge and could yield new information about the anti-metastatic activity of NME1, and more generally about the metastatic process.…”
Section: Nme In Metastasismentioning
confidence: 99%